2020
DOI: 10.1186/s12879-020-05619-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of serum angiotensin-converting enzyme in coronavirus disease 2019

Abstract: Background To explore the clinical significance of serum angiotensin-converting enzyme (ACE) activity in coronavirus disease 2019 (COVID-19). Methods In this retrospective study, a total of 136 consecutive patients with confirmed COVID-19 were recruited. Demographic and clinical data were recorded. The serum ACE activity was measured at baseline and during the recovery phase, and its relationship with clinical condition was analyzed. Results Of the 136 patients with confirmed COVID-19, the 16 severe patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…[ 11 ] It has been suggested that Tocilizumab by the inhibition of IL‐6 receptor may help decrease the mucus secretion in COVID‐19. [ 12 ] As mentioned earlier, beta‐adrenergic blockers decrease IL‐6. It is interesting to note that chronic propranolol administration has been shown to decrease MUC5AC expression and mucus secretion.…”
Section: Beta‐adrenergic Blocker Treatment In Covid‐19: How They Workmentioning
confidence: 94%
See 2 more Smart Citations
“…[ 11 ] It has been suggested that Tocilizumab by the inhibition of IL‐6 receptor may help decrease the mucus secretion in COVID‐19. [ 12 ] As mentioned earlier, beta‐adrenergic blockers decrease IL‐6. It is interesting to note that chronic propranolol administration has been shown to decrease MUC5AC expression and mucus secretion.…”
Section: Beta‐adrenergic Blocker Treatment In Covid‐19: How They Workmentioning
confidence: 94%
“…As mentioned earlier, Tocilizumab may help decrease the mucus secretion in COVID‐19. [ 12 ] Recently National Institutes of Health (NIH) had recommended Remdesivir for COVID‐19 patients who are on supplemental oxygen but not for those who are on mechanical ventilation. NIH has also recommended dexamethasone due to their immunomodulatory role for the COVID‐19 patients who are on mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, baseline serum ACE activity of severe and non-severe COVID-19 patients was decreased compared to normal controls; the lowest levels were noted in the severe group. The respective activities, however, increased in the recovery phase, and the authors concluded that serum ACE activity could be potentially used as a marker to reflect severity of COVID-19 at baseline [ 36 ]. In another study, no association was seen between serum ACE activity and COVID-19; furthermore, serum ACE activity on admission did not reflect disease severity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…High ACE levels in bronchoalveolar lavage (BAL) fluids have been observed in ARDS despite a reduction in serum ACE levels [19]. Though, no study on COVID-19 has actually measured the ACE levels in BAL fluid and ACE protein expression in lungs, a recent study measuring the circulating ACE levels in COVID-19 patients demonstrated decreased circulatory levels of ACE in severe COVID-19 patients that normalizes during the recovery phase [20]. This reduced serum ACE levels may reflect loss of enzyme release from a damaged pulmonary vascular endothelium, but not be the true representative of ACE activity in the lung compartment [20] that may actually be increased [21].…”
Section: Statement Of Hypothesismentioning
confidence: 99%